The effect of entrepreneurial resilience on entrepreneurial success of SME: A study on SME in Zakho independent administration in Kurdistan Region of Iraq (Entrepreneurship Journal for Finance and Business, 2024)
This study explores the impact of entrepreneurial resilience and entrepreneurial success. A researcher conducted a survey of entrepreneurs in small and medium-sized companies in Zakho city in the Kurdistan Region of Iraq to understand the extent to which flexibility affects company growth and success. They used the descriptive analytical approach to analyse the survey data. The questionnaire was the primary approach to data gathering. Data analysis was performed using both SPSS v26 and Smart PLS v 4.0.9. (82) questionnaires were collected from a total of 95 survey cases. The findings of this study show a substantial and statistically significant effect of entrepreneurial resilience on entrepreneurial success. Entrepreneurial resilience is critical to increasing a company's effectiveness and profitability by addressing immediate and continuous difficulties that force it to seek out possibilities, innovate, and face risks. While these results are convincing in the context of the study, it is necessary to be careful when generalizing them to other corporate settings. Further research is recommended to delve deeper into the nuances of entrepreneurial resilience across diverse contexts. This study contributes valuable insights for entrepreneurs seeking to improve performance through entrepreneurial resilience. Through understanding and leveraging forecasting and forcing conditions, organizations can promote better outcomes and achieve success.